Tidally dominated Miocene deltaic deposits and pipe rocks in the Tebessa Basin, eastern Algeria: sedimentological and ichnological characteristics - Mazrou, Samia; Mahboubi, Mohamed (Geologos, 2021)
Analyses of sedimentology, ichnology and depositional environments of Langhian–Tortonian siliciclastic deposits in the southern Tebessa Basin (eastern Algeria) have revealed a tidally dominated deltaic setting with a high concentration of vertical burrows. From south to north, two depositional environments are here distinguished in the Tebessa Basin: a subaerial lower delta plain in the Oum Ali region with the trace fossils Ophiomorpha and Skolithos linearis, and a proximal delta front with numerous Skolithos, situated in the Hjer Essefra area. The occurrence of Skolithos pipe rock in this Miocene subtidal domain is unusual. Pipe rocks have been commonly reported from shallow and well-oxygenated environments, especially from Cambrian strata; their number decreased significantly during the Ordovician, coupled with an increase in biodiversity. Here different deltaic subenvironments and tidal signals that are exceptionally well preserved in outcrops are analysed and interpreted. Different ichnotaxa are briefly described, and the uncommon density and size of Skolithos pipe-rock in these Miocene strata are discussed.